Intermixing of MoS2 and WS2 photocatalysts toward methylene blue photodegradation - Al Qaydi, Maryam; Rajput, Nitul S.; Lejeune, Michael; Bouchalkha, Abdellatif; El Marssi, Mimoun; Cordette, Steevy; Kasmi, Chaouki; Jouiad, Mustapha (Beilstein Journal of Nanotechnology, 2024)
Visible-light-driven photocatalysis using layered materials has garnered increasing attention regarding the degradation of organic dyes. Herein, transition-metal dichalcogenides MoS2 and WS2 prepared by chemical vapor deposition as well as their intermixing are evaluated for photodegradation (PD) of methylene blue under solar simulator irradiation. Our findings revealed that WS2 exhibited the highest PD efficiency of 67.6% and achieved an impressive PD rate constant of 6.1 × 10−3 min−1. Conversely, MoS2 displayed a somewhat lower PD performance of 43.5% but demonstrated remarkable stability. The intriguing result of this study relies on the synergetic effect observed when both MoS2 and WS2 are combined in a ratio of 20% of MoS2 and 80% of WS2. This precise blend resulted in an optimized PD efficiency and exceptional stability reaching 97% upon several cycles. This finding underscores the advantageous outcomes of intermixing WS2 and MoS2, shedding light on the development of an efficient and enduring photocatalyst for visible-light-driven photodegradation of methylene blue.
Keywords: methylene blue; MoS2/WS2 composite; photocatalysis; photodegradation; transition-metal dichalcogenides